Correlation between the Fazekas Scale for the Degree of Leukoaraiosis and the Score on the Mini Mental State Examination (MMSE) for Cognitive Disorders - Nurcholish Akbar Monayo; Junus A.B. Baan; Rafikah Rauf; Andi Alfian Zainuddin; Cahyono Kaelan (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Leukoaraiosis is part of the aging process and an indicator of brain damage in the elderly, which is characterized by cognitive dysfunction. However, the correlation between cognitive impairment and patients with leukoaraiosis is still poorly understood. Purpose: To assess the correlation between the degree of leukoaraiosis and cognitive impairment. Methods: The research was conducted at RSUP. Dr. Wahidin Sudirohusodo, Makassar in May 2022 until the sample was sufficient, using a cross-sectional research design. The study included all patients who were older than 40, who received a magnetic resonance imaging (MRI) test, and who fulfilled the inclusion and exclusion criteria. The Ethics Commission gave its approval to this study. The Fazekas scale was used to measure the severity of leukoaraiosis, and the MMSE score was used to measure cognitive impairment. The application SPSS version 26.0 was used to analyze the data. Univariate tests was used to minimum and maximum values, standard deviation, frequency, percentage, or mean. Bivariate test was used to Spearman's correlation test. bivariate test using Spearman's correlation test. Results: This study consisted of 39 people; 10 people (25.6%) had mild cognitive impairment and 29 people (74.4%) did not have cognitive impairment, 6 people (15.4%) had leukoaraiosis degree, 0, 18 people (46.2%) had leukoaraiosis grade 1 , 10 people (25.6%) had a degree of leukoaraiosis 2, and 5 people (12.8%) had a degree of leukoaraiosis 3. There was a negative correlation between the degree of leukoaraiosis and cognitive impairment (p = 0.008). Conclusion: The degree of leukoaraiosis using the Fazekas scale can be used for early diagnosis of cognitive disorders, so that it can immediately prevent the severity of cognitive disorders.